Unmasking Hereditary Fructose intolerance through growth chart in an infant - Bhandari, Sujeeta; Joshi, Suchita Shrestha; Poudel, Aashis; Pariyar, Rakesh; Bhusal, Sandip (Nepal Mediciti Medical Journal, 2025)
Hereditary Fructose Intolerance (HFI) is a rare autosomal recessive disorder caused by a deficiency of aldolase B, an enzyme essential for fructose metabolism. It often presents in infancy after the introduction of complementary feeding and is frequently underdiagnosed due to nonspecific symptoms. We report a case of a 7-month-old male infant with recurrent vomiting, poor feeding, and failure to thrive. Laboratory investigations revealed elevated transaminases, hypertriglyceridemia, low HDL, and hyperuricemia, while abdominal ultrasound showed hepatomegaly with fatty changes. Clinical suspicion of a metabolic liver disorder prompted genetic testing, which confirmed HFI through identification of a homozygous pathogenic variant (c.469C>T, p.Gln157Ter) in the *ALDOB* gene. Elimination of fructose, sucrose, and sorbitol from the diet led to rapid clinical improvement, including cessation of vomiting within 24 hours and significant weight gain. This case underscores the importance of growth chart monitoring and detailed dietary history in suspecting HFI, especially in resource limited settings.